The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/art.38353
|View full text |Cite
|
Sign up to set email alerts
|

Novel Risk Loci for Rheumatoid Arthritis in Han Chinese and Congruence With Risk Variants in Europeans

Abstract: Objective. To investigate differences in genetic risk factors for rheumatoid arthritis (RA) in Han Chinese as compared with Europeans.Methods. A genome-wide association study was conducted in China with 952 patients and 943 controls, and 32 variants were followed up in 2,132 patients and 2,553 controls. A transpopulation meta-analysis with results from a large European RA study was also performed to compare the genetic architecture across the 2 ethnic remote populations.Results. Three non-major histocompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 44 publications
1
60
0
Order By: Relevance
“…In contrast, the risks of developing an autoimmune disease such as RA seems to be lower upon treatment with DPP4 inhibitors, according to epidemiological studies [136]. A single nucleotide polymorphism (SNP) within an intron of DPP4 has been identified recently as a novel risk locus of RA [137]. However, in-vivo studies with three different DASH inhibitors ameliorated disease symptoms in both wild-type as well as DPP4-deficient F344 rats, implying the involvement of additional DPP4-like enzymes [111].…”
Section: Asthmamentioning
confidence: 99%
“…In contrast, the risks of developing an autoimmune disease such as RA seems to be lower upon treatment with DPP4 inhibitors, according to epidemiological studies [136]. A single nucleotide polymorphism (SNP) within an intron of DPP4 has been identified recently as a novel risk locus of RA [137]. However, in-vivo studies with three different DASH inhibitors ameliorated disease symptoms in both wild-type as well as DPP4-deficient F344 rats, implying the involvement of additional DPP4-like enzymes [111].…”
Section: Asthmamentioning
confidence: 99%
“…The CCR6 gene rs1854853 association was first discovered in a study on a Han Chinese population [13], as the G allele of this polymorphism was associated with the decreased risk of RA. Moreover, genotypes rs1854853 depicted a strong association with Anti-CCP-positive, but not with Anti-CCP-negative RA patients [13].…”
Section: Discussion ____________________________mentioning
confidence: 99%
“…By producing IL-17, a well-known inflammatory cytokine in most autoimmune diseases, Th17 cells play an important role in the pathogenesis of RA [11]. According to studies conducted on RA, some important risk alleles which impact the immune [13,14]. In addition to RA, CCR6 gene SNPs have been associated with Crohn's disease, colorectal cancer, Graves' disease, and psoriasis [15][16][17].…”
Section: Introduction __________________________mentioning
confidence: 99%
See 1 more Smart Citation
“…9,14 An association of sprouty-related EVH1 domain-containing protein 2 (SPRED2) locus was reported in an expanded meta-analysis of six genome-wide association studies in anticyclic citrullinated peptide antibody (anti-CCP)-positive RA patients in Caucasians. 15 In a genome-wide association study of a Han population, 16 the top SNPs at the three nonmajor histocompatibility complex (non-MHC) loci were associated with both ACPA-positive and -negative RA, but the association signals were all stronger in ACPA-positive patients than in ACPA-negative patients. In the same study, the C-C chemokine receptor type 6 variants showed strong association in ACPA-positive RA patients but not in ACPA-negative RA patients, which is consistent with previous studies in White Europeans.…”
Section: Genetic Factors Predisposing To Clinical Subsets Of Acpa-posmentioning
confidence: 99%